She's a lush : a thesis presented in partial fulfilment of the requirements for the degree of Masters in Creative Writing at Massey University, Manawatū, New Zealand - Collette, Mariana (Massey University, 2018)
In this thesis I examine the form of memoir and look at how and why female memoirists use fictional techniques to establish their narrative of problem drinking. Over the last decade, there has been a rise in the number of memoirs being written about the problematic relationship between women and their drinking, yet there is still very little about this topic from a New Zealand perspective. I argue that memoir is an important tool to examine larger social issues through a personal viewpoint and that the use of memoir gives power to women’s voices on particular issues. This thesis is comprised of two parts. Section one is a critical essay entitled ‘Women who Drink and Memoir.’ Section Two is a creative component consisting of a memoir piece entitled ‘She’s a Lush.’ The critical essay examines Drink: The Intimate Relationship between Women and Alcohol by Ann Dowsett- Johnston (2013) ; Lit by Marry Karr (2010); Drinking: A Love Story by Caroline Knapp (1996); Blackout: Remembering the Things I Drank to Forget by Sarah Hepola (2015); A Manual for Cleaning Women by Lucia Berlin (1977) and Mrs D. is Going Without by Lotta Dann (2014), exploring how and why they use social and medical data, metaphor, chronology, characterisation and intimate detail to tell their story of problem drinking. The creative component is my own memoir.
Keywords: Johnston, Ann Dowsett; Drink; Karr, Mary; Lit; Knapp, Caroline; Drinking; Hepola, Sarah; Blackout; Berlin, Lucia; Manual for cleaning women; Dann, Lotta; Mrs D. is going without; Criticism and interpretation; Autobiography; Women authors; Women; Alcohol use; New Zealand; 360201 Creative writing (incl. scriptwriting)